Trabajando en ambos: Toward a Race Radical Mode of Study in Urban Latinx Educational Research and Politics. Issue 14 (December 2021) - Mayorga, Edwin
Background/Context: Over the last 60 years, U.S. Latinxs have become the largest minoritized ethnic groups in the United States and U.S. schools, and despite progress and investments attained through activism in the streets, in the courtroom, in policy, and in research, schools chronically underserve Latinx youth, and they are as undereducated and underprepared today as they were in the 1960s. Findings like low rates of participation in early childhood programs, low graduation rates, and underpreparation for college success have led policymakers and scholars to declare that we are in the midst of a "Latinx education crisis." Purpose/Objective/Research Question/Focus of Study: In this article, I think through the late Jean Anyon's political economic "mode of study" as part of working toward a race radical approach to understanding and addressing the complexities of U.S. Latinx urban education. Setting/Population: The study takes place in the New York City neighborhood of East Harlem (El Barrio) and focuses on individuals and institutions involved in neighborhood politics and education. Research Design: The first half of this article is a theoretical analysis and discussion of Jean Anyon's mode of study. The second half is drawn from a participatory historical ethnography I conducted with the Barrio Education Participatory Action Research (PAR) collaborative (#BarrioEdProject), which was comprised of myself and two college-aged youth co-researchers from El Barrio at the time of the study (2013–2014). The research collaborative designed and implemented the study, which included a series of multigenerational interviews, archival research, and observations of public events. Conclusions/Recommendations: If we are to robustly understand and address these issues, we must engage in a mode of study that attends to the ways the combined forces of capitalism and structural racism, or racial capitalism, give shape to the urban and educational ecosystems. We need to employ ways of knowing that are historical, holistic, and justice oriented.